The impact of pre-natal care for pregnant women in street conditions (Research, Society and Development, 2021)
Introduction: Prenatal care is one of the fundamental pillars for health promotion during pregnancy, promoting care for women, taking into account all the particularities that involve this process. Monitoring during prenatal care is important for prevention, detection and control of complications and should start in the first trimester of pregnancy, but unfortunately, many women, especially those in vulnerable situations, have difficulty access to health services. Objectives: To describe and discuss the importance of prenatal care for homeless women. Methodology: This is an integrative review with a qualitative approach, using the databases PubMed, BVS and SciELO using the descriptors “People living on the streets”; “Pre-Christmas Assistance” and “Pregnant Woman. 76 articles were found, of which 42 met the inclusion criteria and 34 were excluded, and 8 articles were analyzed in the end. Final Considerations: Thus, it is clear that although the SUS has strategies within the PHC for monitoring homeless pregnant women through the eCR, there is still negligence. Furthermore, there is a scarcity of articles in the databases that address the objective of this study, thus it is necessary to encourage more studies to be carried out with PSR as a target audience. Finally, we can see the extreme importance of good prenatal care, especially for people in vulnerable situations, so that injuries and damage are reduced.